2017
DOI: 10.1186/s11658-017-0035-3
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory mechanisms of NG2/CSPG4 expression

Abstract: Neuron-glial antigen 2 (NG2), also known as chondroitin sulphate proteoglycan 4 (CSPG4), is a surface type I transmembrane core proteoglycan that is crucially involved in cell survival, migration and angiogenesis. NG2 is frequently used as a marker for the identification and characterization of certain cell types, but little is known about the mechanisms regulating its expression. In this review, we provide evidence that the regulation of NG2 expression underlies inflammation and hypoxia and is mediated by met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 74 publications
2
53
0
Order By: Relevance
“…Although a full understanding of the physiological roles of CSPG4 is still required, all reports suggest it is ubiquitously involved in multiple tissue development and homeostasis processes, and its roles may be differentially modulated based on the nature of the local tissue microenvironment ( 17 ). The regulation of CSPG4 expression is reported to be strongly affected by inflammatory cytokines such as TNF-α, interleukin (IL)-1α, IFN-γ, and TGF-β and hypoxia-induced mechanisms involving hypoxia-inducible factors.…”
Section: Cspg4 Normal Tissue Distribution Structure and Physiologicmentioning
confidence: 99%
“…Although a full understanding of the physiological roles of CSPG4 is still required, all reports suggest it is ubiquitously involved in multiple tissue development and homeostasis processes, and its roles may be differentially modulated based on the nature of the local tissue microenvironment ( 17 ). The regulation of CSPG4 expression is reported to be strongly affected by inflammatory cytokines such as TNF-α, interleukin (IL)-1α, IFN-γ, and TGF-β and hypoxia-induced mechanisms involving hypoxia-inducible factors.…”
Section: Cspg4 Normal Tissue Distribution Structure and Physiologicmentioning
confidence: 99%
“…Although expressed in >50 cell types, including chondroblasts, osteoblasts, keratinocytes, smooth muscle cells, and macrophages [ 49 , 50 ], NG2/CSPG4 expression seems to be confined to precursor or progenitor cells of epithelial and mesenchymal origin [ 48 ]. In particular, NG2/CSPG4 is not expressed by multipotent stem cells, but is upregulated when a stem cell becomes initially committed to a particular cell lineage.…”
Section: Ng2/cspg4 Expression Patternmentioning
confidence: 99%
“…Although high levels of CSPG4 are frequently used as a marker to identify and predict gliomas, the potential of CSPG4 as a therapeutic target has not been fully explored, and little pharmacologic work has been conducted to elucidate mechanisms regulating its expression (Dawson, Levine, & Reynolds, ). Early studies found that CSPG4 regulated the expression of inflammatory and transcription factors, and these regulatory elements defined CSPG4‐mediated tumourigenesis (Ampofo, Schmitt, Menger, & Laschke, ). Therefore, in anticipation of future therapeutic strategies and developments, the identification of novel agents that can inhibit CSPG4 signalling might be important for the treatment of GBM (Svendsen et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%